QTL analysis of seed iron, zinc, and phosphorus levels in an Andean bean population - Cichy, Karen Ann; Caldas, GV; Snapp, Sieglinde S.; Blair, Matthew W. (Wiley, 2009)
Iron and zinc are essential micronutrients for human health often found in insufficient quantities in the diet. Biofortification of seed crops has been undertaken to reduce micronutrient malnutrition. The objectives of this study were to identify variability for seed Fe, Zn, P, and phytic acid levels in an F5:7 recombinant inbred line (RIL) population developed from a cross between AND696 and G19833, both common beans (Phaseolus vulgaris L.) of Andean origin. Quantitative trait loci (QTL) analysis was conducted with data from 2 yr and 2 P treatments with a previously described linkage map of AND696/G19833. Significant environmental and genetic variability for Fe, Zn, and P levels was identified, and Fe and Zn levels were correlated (up to r=0.53). Quantitative trait loci for seed Fe and Zn co‐localized on three linkage groups (B1, B6, and B11). On B6, a QTL for Fe (R2 = 0.36) was found at the same marker interval as a QTL for seed Zn (R2 = 0.39), both derived from AND696. Quantitative trait loci for seed P were identified on six linkage groups and explained 17 to 55% of the total phenotypic variation depending on year and environment.